DZIKRUL GHOFILIN SEBAGAI MEDIA DAKWAH GUS MIEK - Setiawan, Muhamad Agung (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 17 No 2 (2021)DO - 10.24239/al-mishbah.Vol17.Iss2.253, 2021)
One way to get closer to Allah is through dhikr. Dhikr may let the mind calm and the heart becomes peaceful. One of the islamic preachers who uses dhikr as his da'wah media is Gus Miek, the son of the great cleric of the Al-Fala a h Ploso Islamic boarding school in Kediri, namely KH. Djazuli Uthman. The dhikr media that was initiated by Gus Miek which is still eloquently enlivened is dhikrul ghofilin. The purpose of this study is to explain how dhikrul ghofilin is a media for Gus Miek's da'wah. To get the results of this study, the researcher uses a qualitative method and literature review as the source of the study. The results of this study state that Gus Miek in establishing dhikrul ghofilin as his da'wah media was very successful in attracting Mad'u from all society, the ordinary people, the clerics to the sinners, although there were previously twists and turns that happened because of the controversial founder. Keywords: Dhikr, Da'wah, Media